An unexpected disruption of the atmospheric quasi-biennial oscillation - Osprey, S; Butchart, N; Knight, J; Scaife, A; Hamilton, K; Anstey, J; Schenzinger, V; Zhang, C (American Association for the Advancement of Science, 2016)
One of the most repeatable phenomena seen in the atmosphere, the quasi-biennial oscillation (QBO) between prevailing eastward and westward wind-jets in the equatorial stratosphere (~16-50 km altitude), was unexpectedly disrupted in February 2016. An unprecedented westward jet formed within the eastward phase in the lower stratosphere and cannot be accounted for by the standard QBO paradigm based on vertical momentum transport. Instead the primary cause was waves transporting momentum from the Northern Hemisphere. Seasonal forecasts did not predict the disruption but analogous QBO disruptions are seen very occasionally in some climate simulations. A return to more typical QBO behavior within the next year is forecast, though the possibility of more frequent occurrences of similar disruptions is projected for a warming climate.